2003
DOI: 10.1074/jbc.m302152200
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Membrane Proteolysis by FtsH

Abstract: Escherichia coli FtsH is a membrane-bound and ATPdependent protease responsible for degradation of several membrane proteins. The FtsH action is processive and presumably involves dislocation of the substrate from the membrane to the cytosol. Although elucidation of its molecular mechanism requires an in vitro reaction system, in vitro activities of this enzyme against membrane protein substrates have only been assayed using detergent-solubilized components. Here we report on the construction of in vitro react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…and Ito (46) had shown that GSSG converts in vitro synthesized mature PhoA into an enzymatically active enzyme. Using a complete in vitro approach, we find that exclusively the oxidized form of TorA-PhoA is translocated into INV, a process that is entirely dependent on an active TatABC translocase of the vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…and Ito (46) had shown that GSSG converts in vitro synthesized mature PhoA into an enzymatically active enzyme. Using a complete in vitro approach, we find that exclusively the oxidized form of TorA-PhoA is translocated into INV, a process that is entirely dependent on an active TatABC translocase of the vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Based on studies of FtsH in E. coli (Akiyama and Ito, 2003) and its homologs in mitochondria (Langer, 2000), suggestions can be made for how FtsH (slr0228) and its chloroplast homologs could catalyze D1 degradation. The ATPase activity of FtsH (slr0228), and possibly other homologs, might drive the pulling of damaged full-length D1, or D1 fragments, through a large FtsH pore within the membrane (Shotland et al, 1997).…”
Section: A Possible Conserved Mechanism For D1 Degradation In Cyanobamentioning
confidence: 99%
“…This might reflect the weak and unstable activity of FtsH used in the assay and the difficulty of measuring the small amount of full-length D1 degradation on immunoblots. At a more fundamental level, recent work with E. coli FtsH suggests that it is important to use a membrane system and not detergent-solubilized extracts to reconstitute the FtsH-catalyzed degradation of a membrane protein (Akiyama and Ito, 2003). Therefore, the use of membrane vesicles might be a useful approach in the future to determine whether FtsH alone can degrade full-length damaged D1 in vitro.…”
Section: Analysis Of D1 Degradation In Vitro and In Vivomentioning
confidence: 99%
“…The s 32 protein is stabilized in ftsH-null strains of E. coli, and its levels are at least 20-fold higher than those in wild-type cells . One such strain, AR 5090 (DftsH : : kan, sfhC21), offers an excellent in vivo assay system for monitoring the protease activity of FtsH (Akiyama & Ito, 2000;Karata et al, 2001;Akiyama & Ito, 2003). MsFtsH was expressed from the pT18-MsH recombinant vector in E. coli AR 5090 cells.…”
Section: Degradation Of Smentioning
confidence: 99%